Innovative Loop Design for Effective & Efficient Space Closure: The Swan Loop - Kohli, Sarvraj; Chandrasekhar, Shyamala; Sundari, KK Shantha; Felicita, Sumathi; Kohli, Virinder S (Orthodontic Journal of Nepal, 2012)
Various space closing mechanics have been advocated for fixed appliance orthodontic mechanotherapy, ranging from the use of micro-implants to employing specially designed space closing loops. These techniques have their inherent advantages and disadvantages; primarily with friction-less mechanics it is the intricate wire-bending which dissuades the clinician from everyday usage. Presented in this report is a proposal of an innovative loop which can be readily assimilated in clinical orthodontic practice and is both efficient and effective for controlled space closure scenarios.